ANALISIS PENGARUH RISIKO BANK DAN PUBLIC LISTING TERHADAP PROFITABILITAS BANK UMUM SYARIAH - Indah Jati Utami; Muhamad Syaichu (Faculty of Economics and Business Diponegoro University, 2022)
This study aims to analyze the effect of Financing Risk, Insolvency Risk, Operational Risk, Liquidity Risk, and Public Listing on the profitability of Islamic banks in Indonesia. This study uses a census technique in sampling, where the entire population is used as a sample. This technique was chosen in the hope of providing the characteristics of each element in the population so that it can provide a true picture of Islamic banking in Indonesia. The data is obtained from the reports for the first quarter of 2021 – the first quarter of 2022 on 12 Islamic Commercial Banks (ICB) registered with the Otoritas Jasa Keuangan (OJK). The data analysis method used is multiple linear regression. The results of the analysis that have been carried out can be done partially, the variables of Financing Risk, Insolvency Risk, Operational Risk, have a significant negative effect on Profitability (ROA), while the Liquidity Risk variable has a significant positive effect on Profitability (ROA), the Listing variable has no significant positive effect on Profitability (ROA). The amount of ability to explain the dependent variable given by the independent variable is 58%